Central Odontogenic Fibroma Accompanied by a Central Giant Cell Granuloma-Like Lesion: Report of a Case and Review of Literature - Monir Moradzadeh; Abbas Karimi; Hassan Mirmohammad Sadeghi; Samira Derakhshan; Seyed Mobin Tafreshi; Samar Jalali (Tehran University of Medical Sciences, 2022)
Central giant cell granuloma (CGCG) is a benign non-neoplastic intraosseous lesion mainly found in the anterior mandible. It is characterized by multinucleated giant cells, representing osteoclasts or macrophages. Central odontogenic fibroma (COF) is an uncommon benign lesion of the jaws. It originates from the odontogenic ectomesenchyme. In rare cases, COF may accompany a CGCG. To date, 49 cases of COF accompanied by CGCG-like lesions have been reported in the literature. In this paper, we present another case of COF-CGCG in a 46-year-old female. The lesion was located in the posterior mandible. Excisional biopsy was carried out, and histopathological analysis revealed multinucleated giant cells with numerous strands of odontogenic epithelium. A literature review of previously reported cases was also performed.